Implementasi Model Project Based Learning Dalam Meningkatkan Berpikir Kreatif Siswa Materi Sistem Tata Surya - Sevira Silakhul Mukminah; Rahmat Rudianto; Anarisa (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2025)
The development of education and technology today is very rapid. So that it requires every individual to have high creativity and knowledge, in order to compete with other individuals. The main objective of this study is to improve students' creative thinking skills on the solar system material by using the project based learning model. While the formulation of this study is: 1) How are the activities of teachers and students in implementing the project based learning model on the solar system material. 2) How are students' responses to the implementation of the project based learning model on the solar system material. 3) How are students' creative thinking skills by using the project based learning model on the solar system material. The problem limitation of this study is grade VI students at MI Al-Muklashin Tanjungan Driyorejo Gresik, this study uses the type of Classroom Action Research (CAR). The results of this study indicate that learning using the project based learning model to improve students' creative thinking skills on the solar system material of grade VI at MI Al-Mukhlashin is in accordance with the rules and has increased.